Estudio de la relación entre la enfermedad periodontal y la hipertensión arterial a través de una revisión bibliográfica: evidencia, mecanismos y perspectivas terapéuticas - Zamora Guanopatin, Bryan Stalin (2025)
Both diseases, periodontitis and hypertension share inflammation as a common factor in their pathological development. In periodontal disease, the accumulation of bacterial plaque causes an inflammatory response in the gums, leading to destruction of gingival and bone tissues. In the case of arterial hypertension, elevated blood pressure puts stress on arteries and blood vessels, leading to a chronic inflammatory response that contributes to vascular damage and the development of cardiovascular disease. Objective: Based on the exploration of the relationship between Periodontal Disease and Arterial Hypertension through a Bibliographic Review, which involves analysing the underlying mechanisms linking these two conditions and evaluating the therapeutic perspectives that could arise from this relationship, evidencing different types of Mechanisms and Therapeutic Perspectives. Materials and methods: A total of 6 articles were found in PubMed addressing the association between arterial hypertension and periodontal disease, excluding reviews. In ScienceDirect, 18 papers dealing with therapeutic perspectives on the interconnection between hypertension and periodontal disease were identified. Results: Twenty records were found that address the therapeutic perspectives, interconnection and association between high blood pressure and periodontal disease. These results suggest a significant amount of information available in the selected databases to support the research on the relationship between periodontal disease and hypertension, as well as therapeutic perspectives on this interaction. Conclusions: Highlight the importance of oral health in the prevention of systemic diseases such as high blood pressure. The studies reviewed have highlighted the importance of treating periodontitis as a possible risk factor for the development of high blood pressure. Further research is needed to better understand the underlying mechanisms and to explore new therapeutic perspectives to address the relationship between periodontal disease and hypertension. This article aims to provide a comprehensive understanding of how periodontal disease and hypertension are interconnected, and how this relationship can be used to develop new therapeutic strategies that benefit both oral and cardiovascular health.